Minimally invasive treatment of Peyronie's disease: evidence‐based progress. (July 2014) - Jordan, Gerald H.; Carson, Culley C.; Lipshultz, Larry I.
<x xml:space="preserve">Abstract</x> Peyronie's disease (PD) is often physically and psychologically devastating for patients, and the goal of treatment is to improve symptoms and sexual function without adding treatment‐related morbidity. The potential for treatment‐related morbidity after more invasive interventions, e.g. surgery, creates a need for effective minimally invasive treatments. We critically examined the available literature using levels of evidence to determine the reported support for each treatment. Most available minimally invasive treatments lack critical support for effectiveness due to the absence of randomised, placebo‐controlled trials (RCTs) or non‐significant results after RCTs. Iontophoresis, oral therapies (vitamin E, potassium para‐aminobenzoate, tamoxifen, carnitine, and colchicine), extracorporeal shockwave therapy, and intralesional injection with verapamil or nicardipine have shown mixed or negative results. Treatments that have decreased penile curvature deformity in Level 1 or Level 2 evidence‐based, placebo‐controlled studies include intralesional injection with interferon α‐2b or collagenase clostridium histolyticum.